(3dhGbM GdCfhGQ aj WHbGJ GdCNjGQs - (3YHO GdhgGH Hf CMeO Hf Ydj GdMfaj, fSHg Edj eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO,J (B973 (3g` s
(3ChdgG (B:s
(3hHYO , agPG cJGH dNUJ ajg WHbGJ LeGYI ef GdChdjGA GdPjf jbJOi Hge ai WQjb Gddg YR hLd ef GdUMGHI hGdJGHYjf s
(3BNQgG (B:s
(3hCeG ef GTJgQ HGdYHGOI hGdRgO hGdhQY cGdTjN CHj ESMGb GdTjQGRj hGdEeGe Gdfhhi, abO GcJajJ HTgQJge HPdc , QVi Gddg Yfge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B218s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B338 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B466 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B361 s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs